GT-57633 catalogue of Martian impact craters developed for evaluation of crater detection algorithms - Salamuniccar, G; Loncaric, S (Planetary and space science, 2008)
Crater detection algorithms (CDAs) are an important subject of the recent scientific research. A ground truth (GT) catalogue, which contains the locations and sizes of known craters, is important for the evaluation of CDAs in a wide range of CDA applications. Unfortunately, previous catalogues of craters by other authors cannot be easily used as GT. In this paper, we propose a method for integration of several existing catalogues to obtain a new craters catalogue. The methods developed and used during this work on the GT catalogue are: (1) initial screening of used catalogues; (2) evaluation of self-consistency of used catalogues; (3) initial registration from three different catalogues; (4) cross-evaluation of used catalogues; (5) additional registrations and registrations from additional catalogues; and (6) fine-tuning and registration with additional data-sets. During this process, all craters from all major currently available manually assembled catalogues were processed, including catalogues by Barlow, Rodionova, Boyce, Kuzmin, and our previous work. Each crater from the GT catalogue contains references to crater(s) that are used for its registration. This provides direct access to all properties assigned to craters from the used catalogues, which can be of interest even to those scientists that are not directly interested in CDAs. Having all these craters in a single catalogue also provides a good starting point for searching for craters still not catalogued manually, which is also expected to be one of the challenges of CDAs. The resulting new GT catalogue contains 57,633 craters, significantly more than any previous catalogue. From this point of view, GT-57633 catalogue is currently the most complete catalogue of large Martian impact craters. Additionally, each crater from the resulting GT-57633 catalogue is aligned with MOLA topography and, during the final review phase, additionally registered/aligned with 1/256° THEMIS-DIR, 1/256° MDIM and 1/256° MOC data-sets. Accordingly, the resulting GT-57633 catalogue can successfully be used as a part of the framework for evaluation of CDAs.